2020
DOI: 10.1002/ange.202013257
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Carbon Dioxide and Iron Oxide in Molten Salts to Fe/Fe3C Modified Carbon for Electrocatalytic Oxygen Evolution

Abstract: Non-noble electrocatalyst for the oxygen evolution reaction (OER) is essential for water electrolysis and electrochemical conversion of CO 2. Integrating electrochemical fixation of CO 2 and electrochemical metallurgy to prepare advanced OER electrocatalyst is a promising solution to promote carbon neutrality and renewable energy. Herein, the electrochemical reduction of CO 2 and Fe 2 O 3 are combined in molten salts to prepare cathodic Fe 3 C-based electrocatalyst and anodic oxygen at 600 8C with enhanced cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The SEM images of NiFe 2 O 4 before and after electrolysis in Figure S14 show that the morphology was not changed by the reconstitution of the alkaline electrolyte, but the reconstituted species was unstable in pure water, which increased the surface roughness of the nanoparticles. The Raman spectra of NiFe 2 O 4 in Figure S15 demonstrated that more Ni/FeOOH was generated on the catalyst surface after pre-activation which is stable in pH = 14; however, the intensity of the FeOOH peak located at ∼680 cm –1 decreased after the test in pure water, implying the dissolution of Fe species Figure S16 gives the dissolved metal content in the electrolyte after the 20 h stability test of NiFe 2 O 4 and Ni 0.5 Co 1.5 FeO 4 with or without the pre-activation.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM images of NiFe 2 O 4 before and after electrolysis in Figure S14 show that the morphology was not changed by the reconstitution of the alkaline electrolyte, but the reconstituted species was unstable in pure water, which increased the surface roughness of the nanoparticles. The Raman spectra of NiFe 2 O 4 in Figure S15 demonstrated that more Ni/FeOOH was generated on the catalyst surface after pre-activation which is stable in pH = 14; however, the intensity of the FeOOH peak located at ∼680 cm –1 decreased after the test in pure water, implying the dissolution of Fe species Figure S16 gives the dissolved metal content in the electrolyte after the 20 h stability test of NiFe 2 O 4 and Ni 0.5 Co 1.5 FeO 4 with or without the pre-activation.…”
Section: Resultsmentioning
confidence: 99%
“…Benefitting from the high concentration of O 2− in molten carbonates, we can (electro-)chemically synthesize oxide functional materials in molten salts. 119,120 The molten salt can serve as both a promising electrolyte and solvent to electrochemically break the chemical bonds of LTMO, and thereby separate Li-and transition metal species.…”
Section: High-temperature Molten Salt (Electro-)chemistrymentioning
confidence: 99%
“…Usually, LiFePO 4 prefers to be oxidized to FePO 4 with the retention of olivine structure and Li is selectively recycled. The oxidation agents are [Fe(CN) 6 ], 3–122 Na 2 S 2 O 8 , 123,124 Fe 2 (SO 4 ) 3 , 125 H 2 O 2 , 126 and air. 127 The oxidation roasting of LiFePO 4 in the air generates Fe 2 O 3 and Li 3 Fe 2 (PO 4 ) 2 , 128 by which the Li and Fe cannot be separated completely.…”
Section: Cathode Materials Recoverymentioning
confidence: 99%